Variabilidade genética e caracterização de híbridos de Jatropha curcas L. oriundos de cruzamentos dialélicos - Ribeiro, Daniel Ornelas (2018)
The species Jatropha curcas L. has a good yield of oil for biodiesel production. It has a resistance to water stress and it demonstrates a great potential as an insecticidal or medicinal agent. However, much research is still needed on the multiple uses of this species. Thus, whilst aiming to characterize 10 specific hybrids of J. curcas, the following assessments were carried out: i) a technological prospection regarding the bioactive properties of the Jatropha curcas L. species; ii) estimations of genetic diversity; iii) morphoagronomic characterizations of the fruits and seeds; and iv) the initial seed quality evaluations of the 10 hybrids of J. curcas that originated from diallel crosses. The survey was conducted in the databases of scientific, technological and patent research, on the websites of the Ministry of Health and the Ministry of Agriculture, Livestock and Supply, as well as on the National Agency of Sanitary Surveillance (ANVISA) website. The estimations of the genetic variabilities were performed by using Inter Simple Sequence Repeat (ISSR) molecular markers. Nine primers were used and six were selected with an 80.7% polymorphism. The morphoagronomic characterizations and the estimations of the phenotypic correlations between the variables were determined and deployed through track analyzes. The genetic, environmental, heritability and heteroses variances of the hybrids were estimated. In order to extract the oil, petroleum ether solvents were used and a Soxhlet type apparatus was also used. These obtained samples were derivatized and analyzed by gas chromatography coupled to mass spectrometry (GC-MS). Regarding the technological prospecting, there were academic records on the use of these extracts from different parts of J. curcas, evidencing the importance of this species for the formulation of phytosanitary products. However, there were only a few patent records regarding the use of these extracts as an insecticide. The average genetic similarity between the hybrids was 58.4%, with a greater genetic diversity observed between the 1x5 and 1x8 hybrids and with a greater similarity between the 3x13 and 1x5 hybrids. Morphoagronomically, the hybrids differed in their biometry, as well as in the oil contents of their seeds. A high heritability was observed for their agronomical characteristics, except for the mass of 100 seeds. The 1x5 hybrids stood out for their biometric characteristics. The highest oil content was extracted from the 3x13 hybrid seeds. The highest percentages that were found in the fatty acids were oleic acid (35.7% to 38.9%) and linoleic acid (30.6% to 37.8%). For their germination, the 1x5 (56%), 1x8 (55%), 1x13 (56%), 3x8 (61%), 4x5 (56%) and 4x8 (61%) hybrids stood out in the two evaluated years. As for their IVG, the highest values were observed in the 1x5 (3.34), 1x13 (3.70), 3x8 (3.34), 3x13 (3.05) and 4x8 (3.69) hybrids. The tetrazolium test verified that among the seeds that did not germinate, the hybrids 1x5, 3x5, 3x8 and 3x13 were not viable.